From Pre-Service to Employed Teacher: Examining One Year Later the Benefits and Challenges of a Co-Teaching Clinical Experience - Guise, Megan; Thiessen, Krystal (Educational (Re)naissance, 2017)
The research study described in this article is an extension of a yearlong mixed methods study of eight co-teaching pairs (four English and four science) and their implementation of co-teaching during the clinical experience. A year after these eight pre-service teachers participated in the co-teaching research study while enrolled in a teacher education program, they were interviewed at the conclusion of their first year of employed teaching with the goal of exploring the impact that the co-teaching experience had on their development as a teacher. Findings reveal that co-teaching during the clinical experience provides an opportunity to shape pre-service teachers to be collaborative, reflective practitioners who seek out opportunities to collaborate and position themselves as lifelong learners. However, teacher education programs that implement co-teaching during the clinical experience have a responsibility to ensure that co-teaching occurs with fidelity and that pre-service teachers are supported to transition to full-time employment where the day-to-day co-teaching opportunities may be more limited.